ANALYSIS OF LEARNING STRATEGY MASTERY TO IMPROVE PROFESSIONAL COMPETENCE OF INDONESIAN LANGUAGE TEACHERS IN THE 5.0 ERA - Eka, Eka Sofia Agustina (Universitas Negeri Surabaya, 2025)
The rapid development of the industrial revolution has brought about rapid changes in the world of education. The systems and subsystems in the field of education also adapt to these developments following the dynamics of changes in world technology. The most specific thing is in education at all levels of formal education in Indonesia, more specifically in learning Indonesian. The most important element in achieving optimal learning in Indonesian language subjects depends on the capacity of teachers or educators in transferring Indonesian language knowledge. The substance of Indonesian language subjects is mapped into two components, namely language and literature. Teachers in the 5.0 era must be very able to adapt to matters related to technological developments. Some technological components that are very important for Indonesian language teachers to learn are the use of LMS (learning management systems), learning applications, the use of social media to share information and collaborate, and the use of teaching aids whose purpose is to increase the effectiveness of learning. However, apart from that, in essence Indonesian language teachers must have a solid understanding of the nature of Indonesian language learning in the context of its learning, the nature of language proficiency, the nature of language skills, and an understanding of strategies for fostering the acquisition of Indonesian as a second language in the classroom.